Efficacy of pectin-based caproic acid, caprylic acid, linalool, and cuminaldehyde coatings in reducing Salmonella Heidelberg on chicken eggs - Pellissery, Abraham Joseph; Vinayamohan, Poonam Gopika; Xue, Jingyi; Wang, Xinhao; Viju, Leya Susan; Joseph, Divya; Luo, Yangchao; Donoghue, Ann M.; Venkitanarayanan, Kumar (Frontiers in Sustainable Food Systems, 2022)
Among the animal derived food products, contamination of poultry eggs, and egg shell surface is one of the major causes for foodborne salmonellosis in the United States. As a means of reducing the pathogen transfer to the internal egg contents, polysaccharide-based coatings containing antimicrobial phytochemicals could potentially serve as a biocontrol strategy for shelled egg products. The current study investigated the efficacy of four GRAS (Generally Recognized as Safe)-status plant-derived compounds, namely, caproic acid (CAO), caprylic acid (CAY), linalool (LIN) and cuminaldehyde (CUM), as pectin-based coating treatments, individually or in combination, for reducing Salmonella Heidelberg (SH) on shell eggs. A three-strain mixture of SH (~8.0 log CFU in 50 μL inoculum) was spot-inoculated on surface sterilized white-shelled eggs. Eggs were evenly coated with either pectin-based treatments of CAO (1%), CAY (1%), LIN (1%) and CUM (1%), individually, or a combination of 4 phytochemicals (COMB- each phytochemical at 0.5% v/v level of inclusion). The treated eggs were stored at 4°C and SH counts were enumerated on days 0, 1, 3, 5, 7, 14, and 21 of storage. The study was replicated thrice, 3 eggs/treatment/day time point, and the data were analyzed using two-way ANOVA with significance tested at p < 0.05. On day 0, pectin-coated control eggs had ~7.6 log CFU of SH/egg. At the end of refrigerated storage (day 21), pectin-based coating of CAO and CAY at 1% level reduced SH by 2.0–2.5 log CFU/egg (P < 0.05) when compared to controls. In addition, the CUM and LIN based coatings produced 3.0 log and 3.9 log reduction, respectively, in SH counts on eggs by day 21 of storage. Among the treatments with phytochemical combinations, COMB1 [pectin (2%) + Caprylic acid, caproic acid and cuminaldehyde (each at 0.5% level)] was found to be most effective, reducing SH counts to 2.5–3.3 log CFU/egg from day 0 through day 14, and by the end of storage period (day 21), a 3.5 log CFU reduction/egg (p < 0.05) compared to untreated controls. Morphological studies of treated eggs using atomic force microscopy (AFM) have shown that the roughness of eggs can be influenced by a combination of various compounds. Results indicate the potential efficacy of the aforesaid phytochemicals in reducing SH on shell eggs; however, further studies investigating their industrial feasibility and effects on sensory attributes of eggs are warranted.